Globalization and Nationalism - Natalie Sabanadze (Central European University Press, 2010)
Argues for an original, unorthodox conception about the relationship between globalization and contemporary nationalism. While the prevailing view holds that nationalism and globalization are forces of clashing opposition, Sabanadze establishes that these tend to become allied forces. Acknowledges that nationalism does react against the rising globalization and represents a form of resistance against globalizing influences, but the Basque and Georgian cases prove that globalization and nation...